Evaluating Conflict Dynamics: A Novel Empirical Approach to Stage Conceptions. (April 2018) - Jones, Benjamin T.; Metzger, Shawna K.
Interest in processes has become increasingly pronounced in international conflict research in recent years, especially how these processes unfold across time "dynamics". We focus in particular on "stage conceptions" of dynamics: processes that unfold over a series of sequential, and possibly recurrent, stages. We suggest that stage conceptions have two key properties: plurisectality and conditional covariate effects. We propose a novel econometric application to quantitatively assess claims regarding stage conceptions of dynamics: survival modeling. Specifically, we use multistate models to examine how a process evolves through its individual stages, and also whether covariate effects differ across these stages. We use Huth and Allee's territorial dispute data to demonstrate the importance of conceptualizing conflict as a dynamic process, as well as empirically modeling it as such. We show democracy has different effects on dispute resolution, depending on the dispute's stage, but that these different effects disappear after time passes.